Bangka Marine Pollution: Oil Spill towards ASEAN Working Group on Coastal and Marine Environment - Winanda Kusuma; Reko Dwi Salfutra; Lili Liana; Ave Agave Christina Situmorang (International Law Discourse in Southeast Asia, 2026)
Marine areas pollution, which is also an urgent problem for ASEAN. Indonesia is very vulnerable to risk of oil spills and the heavy flow of tanker traffic in Indonesia's maritime waters. Oil spill pollution 2024 at Bangka Belitung Sea polluting a number of coastal areas. The polluted area of the Bangka Islands is one of the agendas that must be resolved. For this reason, it is necessary to have a legal study to maintain ecosystem in accordance with ASEAN cooperation, especially ASEAN WGCME in marine protect the sea in ASEAN sea. This study adopts a normative legal research method, a conceptual approach. Through this study, it is known that oil spills are widely recognized as one of the sources of marine pollution in ASEAN sea as a negative impact of human activities in the sea. The sea area of Bangka periodically experiences oil pollution. The pollution that occurs in the Bangka sea area is not solved systematically, the origin and loss of pollution is unknown. This damage can be effectively resolved through collaboration and cooperation. The ASEAN WGCME should be developed to become a legal standard in protecting the coastal and marine environment of the ASEAN region.